Role of prelimbic cortex PKC and PKMζ in fear memory reconsolidation and persistence following reactivation - da Silva, Thiago Rodrigues (Sci Rep, 2020)
The persistence of newly acquired memories is supported by the activity of PKMζ, an atypical isoform of protein kinase C (PKC). Whether the activity of conventional and atypical PKC isoforms contributes to reactivated memories to persist is still unknown. Similarly, whether memory reactivation is a prerequisite for interventions to be able to change memory persistence is scarcely investigated. Based on the above, we examined the role of conventional and atypical PKC isoforms in the prelimbic cortex in reconsolidation and persistence of a reactivated contextual fear memory in male Wistar rats. It is shown that (i) inhibiting the PKC activity with chelerythrine or the PKMζ activity with ZIP impaired the persistence of a reactivated memory for at least 21 days; (ii) ZIP given immediately after memory reactivation affected neither the reconsolidation nor the persistence process. In contrast, when given 1 h later, it impaired the memory persistence; (iii) chelerythrine given immediately after memory reactivation impaired the reconsolidation; (iv) omitting memory reactivation prevented the chelerythrine- and ZIP-induced effects: (v) the ZIP action is independent of the time elapsed between its administration and the initial memory test. The results indicate that prelimbic cortex PKC and PKMζ are involved in memory reconsolidation and persistence.